Analysis of transformational leadership effect towards organisational citizenship behaviour mediated by organisational commitment in the heritage hotel. (2018) - ,; Azzuhri, Misbahuddin
Many organisations are shifting the pattern of their leadership style from transactional into transformational leadership as a way of achieving the strategy and goals. This study aimed to analyse transformational leadership influence on organisational citizenship behaviour (OCB) and organisational commitment role in mediating its effects. The type of research is explanatory research with a quantitative approach. The populations in this study are 82 employees from the heritage hotel in Malang, East Java, Indonesia. Census method is used and involves the entire population as respondents. Data are processed by structural equation modelling (SEM) analysis that conducted by the partial least square (PLS) method. The results indicated that transformational leadership has a significant positive effect on OCB and against organisational commitment, where organisational commitment does not much affect OCB. Evidently, organisational commitment does not mediate the effect of transformational leadership on OCB.